Construções condicionais insubordinadas com a conjunção se no português: uma análise diacrônica à luz da gramática de construções - Coradini, Maria Carolina (2022)
Insubordinate constructions have been described as the independent and conventionalized use of formally subordinate clauses (EVANS, 2007). These are cases such as “Se soubesse como me faz sofrer!” (Corpus do Português). According to Evans (2007), these constructions are the result of originally subordinate clauses reanalyzed as independent constructions, after the ellipsis of the main clause. In this work, it is analyzed if-insubordinate conditional constructions in Portuguese, ranging from the 15th to the 20th century, in order to verify i. how many and what are the if-insubordinate construction types; ii. what are the processes involved in their emergence; iii. their productivity over the centuries. The presented analysis is quali-quantitative and based on the theoretical assumptions of Construction Grammar. In this sense, formal and functional aspects of the constructions are considered in the analysis and concepts such as constructional network, schematicity, compositionality and productivity are evoked. Based on a large sample of written language data collected from the corpora Corpus do Português (DAVIES; FERREIRA, 2006) and Tycho Brahe Parsed Corpus of Historical Portuguese (GALVES; ANDRADE; FARIA, 2017), it is proposed a functional classification for these constructions containing the following categories: deontic, evaluative, argumentative, assertive, reasoning, post-modifier and metatextual. The quantitative analysis reveals, from 1.838 diachronic instances, mostly distributed between the 19th and 20th centuries, that there is a tendency in Portuguese of these constructions projecting scenarios resulting from the realization of a potential State-of-Affairs, via deontic constructions of desire and constructions of reasoning, and acting upon discourse organization, via metatextual constructions. Deontic and reasoning constructions account for 45.7% of the cases found in the corpus ranging from the 15th to the 20th century, whereas metatextual constructions account for 25.7% of them. These three appear to be the most productive among the types of insubordinate conditional constructions, adding together 71.4% of the collected data sample. The diachronic data allow to observe that these constructions go through an insubordination path, which points to the loss of conditional meaning. As insubordinate conditional constructions advance along this path, becoming more syntactically independent, they come to express metatextual meanings that overlap the original conditionality of the construction, as they reach a stage of non-compositionality. The loss of conditionality directly reflects on the organization of insubordinate conditionals in a network structure, since it imposes restrictions on the generalization of a common meaning among them. Data also suggest that insubordinate conditionals can emerge both through the ellipsis of main clauses, corroborating the Evans’ (2007) hypothesis, and through processes such as neoanalysis and analogization, in cases of highly conventionalized constructions, that, however, seem not to have less advanced stages of specialization in diachrony.